2020
DOI: 10.1177/0017896920949597
|View full text |Cite
|
Sign up to set email alerts
|

Improving educator’s knowledge and confidence to teach infection prevention and antimicrobial resistance

Abstract: Objective: e-Bug is a teaching resource that addresses the UK 5-year National Action Plan on antimicrobial resistance (AMR) that pledges to work with educators and local authorities to ensure young people understand infection prevention and control (IPC) and AMR. This study aimed to evaluate the effectiveness and acceptability of the e-Bug face-to-face train-the-trainer intervention with school and community educators. Design: Service evaluation of an educational intervention via surveys. Setting: Workshops we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The study found that the e-Bug train-the-trainer intervention significantly improved the confidence, knowledge and skills of educators to teach IPC and AMR topics to children, particularly among teachers without a scientific background. This study supports previous work (Eley et al, 2020; Hayes et al, 2021a) with primary educators and e-Bug training, and also evaluates the wider social and health outcomes following training.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The study found that the e-Bug train-the-trainer intervention significantly improved the confidence, knowledge and skills of educators to teach IPC and AMR topics to children, particularly among teachers without a scientific background. This study supports previous work (Eley et al, 2020; Hayes et al, 2021a) with primary educators and e-Bug training, and also evaluates the wider social and health outcomes following training.…”
Section: Introductionsupporting
confidence: 87%
“…The study found a significant improvement in IPC and AMR knowledge in students following use of the e-Bug teaching pack in schools. In a recent study (Hayes et al, 2021a), IPC and AMR knowledge were evaluated in educators following face-to-face e-Bug train-the-trainer intervention via pre and post questionnaires. The study found that the e-Bug train-the-trainer intervention significantly improved the confidence, knowledge and skills of educators to teach IPC and AMR topics to children, particularly among teachers without a scientific background.…”
Section: Introductionmentioning
confidence: 99%
“…During piloting of second-stage prototypes, it became apparent that educators who would deliver food hygiene and safety education had varied backgrounds and training, and required different levels of support to teach certain topics (Hayes et al, 2021). This resulted in the development of background information and instructional sheets, and educator training resources.…”
Section: Discussionmentioning
confidence: 99%
“…Such practice is common in other countries including the United States. Previous study has demonstrated that a ‘train-the-trainer’ approach could enhance trainers’ knowledge on AMR [ 39 ]. Educational programs led by healthcare students in raising public awareness on proper antibiotic use was shown to be effective in increasing patient knowledge on the issue [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%